Warrant in contemporary epistemology essays in honor of Plantinga's Theory of knowledge (Studies in epistemology and cognitve theory, 1996)
In his widely influential two-volume work, Warrant: The Current Debate and Warrant and Proper Function, Alvin Plantinga argued that warrant is that which explains the difference between knowledge and true belief. Plantinga not only developed his own account of warrant but also mapped the terrain of epistemology. Motivated by Plantinga's work, fourteen prominent philosophers have written new essays investigating Plantingian warrant and its contribution to contemporary epistemology. The resulting collection, representing a broad array of views, not only gives readers a critical perspective on Plantinga's landmark work, but also provides in one volume a clear statement of the variety of approaches to the nature of warrant within contemporary epistemology and to the connections between epistemology and metaphysics. Positions covered include internalism and externalism, reliabilism, coherentism and foundationalism, virtue theories, and defensibility theories. Alvin Plantinga responds to the essays in a concluding chapter. Warrant in Contemporary Epistemology will be of interest to all philosophers as well as to upper-level students of epistemology.